دراسة تحليلية للفروق في مهارات إدارة الصف بين التعليم الثانوي العام والمهني "دراسة ميدانية في مدارس محافظة اللاذقية" - شمعون, هنادي; سليمون, ريم; هارون, ظلال (Latakia University Journal - Economic and Legal Sciences Series, 2013)
هدف البحث إلى تحديد أهم المهارات التي تتوفر لدى مدرسي التعليم العام والمهني، والتعرف على الفروق بينهما في الثانوية العامة والمهنية والأثر الذي يعكسه على العملية التعليمية من خلال رفع مستوى خريجيه وإعدادهم للحياة المعاصرة لتأدية الأدوار التي يتوقعها المجتمع منهم، لذلك تناولت الدراسة الحالية ثلاث مهارات أساسية تتمثل المهارة الأولى بتخطيط الدروس باعتبارها من أهم الخطوات التي إذا ألمّ بها المدرس يكون متمكناً من مهارات الدرس جميعها، ومهارة استخدام الوسائل التعليمية، ومهارة إثارة الدافعية لدى الطلاب. واستخدم المنهج الوصفي التحليلي، حيث وزعت استبانة للمدرسين في الثانويات العامة والمهنية للوقوف على مدى إلمامهم بها، ورصد الفروق بين كلا النظامين، وتم التوصل إلى مجموعة من النتائج والتوصيات كان من أهمها وجود فروق تعود لصالح المدرسين في التعليم العام من ناحية امتلاكهم لمهارات التدريس وتطبيقهم لها بشكل أكبر من التعليم المهني، الأمر الذي تطلب ضرورة إعادة النظر في إعداد المدرسين وتأهيلهم لرفع مستوى مخرجات العملية التعليمية. The goal of research is to identify the most important skills that are available to teachers of general and vocational education, and to identify the differences between them in high school and professional impact reflected in the educational process by raising the level of its graduates and prepare them for contemporary life to perform the roles expected by the community of them, so I dealt with the current study three basic skills The first skill is planning lessons as one of the most important steps that if pain be versed teacher of the lesson all the skills, and the skill of using teaching aids, and the skill to raise students' motivation. And use descriptive analytical method, where the distributed questionnaire for teachers in high schools, public and professional to determine the extent of their knowledge, and monitor the differences between both systems, was reached on a set of findings and recommendations was the most important differences exist back in favor of teachers in public education in terms of possession for teaching skills and their application have greater use of vocational education, which required the need to reconsider in the preparation of teachers and rehabilitation to raise the level of the outputs of the educational process.